Tetracationic Gallium Cluster Cations. Issue 43 (2nd October 2018) - Glootz, Kim; Kratzert, Daniel; Himmel, Daniel; Kastro, Aho; Yassine, Zeinab; Findeisen, Tobias; Krossing, Ingo
Abstract: The univalent salt Ga(PhF)2 + [Al(OR F )4 ] − (R F =OC(CF3 )3 ) forms the strongly metal–metal bonded cluster tetracations [Ga II 2 (L)4 ] 4+ and [Ga I 4 (L′)8 ] 4+, when it reacts with innocent ligands like phenanthroline (L=phen) or t ‐butylisonitrile (L′= t Bu‐NC). Their structures and energetics are discussed as a function of the employed ligands, supported by DFT calculations and Born–Fajans–Haber cycles. Abstract : Charging up, but why? Addition of the ligands phenanthroline (phen) or t Bu‐NC to Ga I (PhF)2 + yields the di‐ and tetranuclear cluster tetracations [Ga2 (phen)4 ] 4+ and [Ga4 (CN‐ t Bu)8 ] 4+ with [Ga II 2 ] 4+ and [Ga I 4 ] 4+ cluster cores. Their formation and stability versus a Coulomb explosion was analyzed and rationalized.